Of bicycles, bakelites, and bulbs : toward a theory of sociotechnical change - Bijker, Wiebe E. (Cambridge (Mass.) : MIT press, 1995)
Geeft een omschrijving van de sociale inpakt van technologische uitvindingen
Keywords: Baekeland, Leo Hendrik, -- 1863-1944.; Technology -- Social aspects